TPN IN OBSTETRICS - Huamán G., Moisés (2015)
Two cases of pregnant women treated with total parenteral nutrition (TPN) for addisonian crisis and gravidarum, respectively, making a brief review of this interesting topic, as well as indications of the NPT in obstetrics hiperemessis is presented. Our report is the first in Peru.